Fighting global warming: Is trade policy in Latin America and the Caribbean a help or a hindrance? - Marcelo Dolabella; Mauricio Mesquita Moreira (Inter-American Development Bank (IDB), 2022)
The dire prospects of global warming have been increasing the pressure on policymakers to use trade policy as a mitigation tool, challenging trade economists' canonical "targeting principle." Even though the justifications for this stance remain as valid as ever, it no longer seems feasible in a world that is already engaging actively in using trade policy for climate purposes. However, the search for second-best solutions remains warranted. In this paper, we focus on the climate benefits of tariff reform for a broad sample of Latin American and Caribbean countries, drawing on Shapiro's (2021) insights about the environmental bias of trade policy. Using a partial equilibrium approach and GTAP 10-MRIO data for 2014, we show that even though there is evidence of a negative bias toward "dirty goods" in half of the countries studied, translating this into actionable tariff reforms is plagued by interpretation and implementation difficulties, as well as by jurisdictional and efficiency trade-offs. There are also questions about their efficacy in curbing greenhouse gas emissions.
Keywords: F13; F14; F18; H23; Q56; 330; Trade Policy; International Trade; Climate Change; Latin America andthe Caribbean